A Novel End-To-End Network for Reconstruction of Non-Regularly Sampled Image Data Using Locally Fully Connected Layers - Grosche, Simon; Brand, Fabian; Kaup, André (23rd International Workshop on Multimedia Signal Processing (MMSP), 2021)

Boosting Compressed Sensing Using Local Measurements and Sliding Window Reconstruction - Grosche, Simon; Regensky, Andy; Seiler, Jürgen; Kaup, André (IEEE Transactions on Image Processing, 2020)

Component-Wise Power Estimation of Electrical Devices Using Thermal Imaging - Herglotz, Christian; Grosche, Simon; Bharadwaj, Akarsh; Kaup, André (IEEE Transactions on Consumer Electronics, 2021)
This paper presents a novel method to estimate the power consumption of distinct active components on an electronic carrier board by using thermal imaging. The components and the board can be made of heterogeneous material such as plastic, coated microchips, and metal bonds or wires, where a special coating for high emissivity is not required. The thermal images are recorded when the components on the board are dissipating power. In order to enable reliable estimates, a segmentation of the thermal image must be available that can be obtained by manual labeling, object detection methods, or exploiting layout information. Evaluations show that with low-resolution consumer infrared cameras and dissipated powers larger than 300 mW, mean estimation errors of 10% can be achieved.
CRIS-Team WoS Importer:2021-12-31

Design Techniques for Incremental Non-Regular Image Sampling Patterns - Grosche, Simon; Seiler, Jürgen; Kaup, André (IEEE International Conference on Imaging Systems and Techniques (IST), 2018)

Dynamic Image Sampling Using a Novel Variance Based Probability Mass Function - Grosche, Simon; Koller, Michael; Seiler, Jürgen; Kaup, André (IEEE Transactions on Computational Imaging, 2020)

Enhanced Image Reconstruction From Quarter Sampling Measurements Using an Adapted Very Deep Super Resolution Network - Grosche, Simon; Fischer, Kristian; Brand, Fabian; Seiler, Jürgen; Kaup, André (IEEE International Conference on Image Processing (ICIP), 2020)

Fast Reconstruction of Three-Quarter Sampling Measurements Using Recurrent Local Joint Sparse Deconvolution and Extrapolation - Grosche, Simon; Regensky, Andy; Sinn, Alexander; Seiler, Jürgen; Kaup, André (IEEE Transactions on Circuits and Systems II: Express Briefs, 2022)

Image Super-Resolution Using T-Tetromino Pixels - Grosche, Simon; Regensky, Andy; Seiler, Jürgen; Kaup, André (Proceedings of the IEEE/CVF Conference on Computer Vision and Pattern Recognition (CVPR), 2023)

Iterative Optimization of Quarter Sampling Masks for Non-Regular Sampling Sensors - Grosche, Simon; Seiler, Jürgen; Kaup, André (25th IEEE International Conference on Image Processing (ICIP), 2018)

Lateral spin transport in paraxial beams of light - Neugebauer, Martin; Grosche, Simon; Rothau, Sergej; Leuchs, Gerd; Banzer, Peter (Optics Letters, 2016)
We investigate the lateral transport of (longitudinal) spin angular momentum in a special polarization tailored light beam composed of a superposition of a y-polarized zero-order and an x-polarized first-order Hermite-Gaussian mode. This phenomenon is linked to the relative Gouy phase shift between the individual modes upon propagation, but can also be interpreted as a geometric phase effect. Experimentally, we demonstrate the implementation of such a mode and measure the spin density upon propagation.

Novel Consistency Check for Fast Recursive Reconstruction of Non-Regularly Sampled Video Data - Grosche, Simon; Seiler, Jürgen; Kaup, André (IEEE International Conference on Image Processing (ICIP), 2021)

Real-Time Frequency Selective Reconstruction through Register-Based Argmax Calculation - Regensky, Andy; Grosche, Simon; Seiler, Jürgen; Kaup, André (IEEE International Workshop on Multimedia Signal Processing (MMSP), 2020)
Frequency Selective Reconstruction (FSR) is a state-of-the-art algorithm for solving diverse image reconstruction tasks, where a subset of pixel values in the image is missing. However, it entails a high computational complexity due to its iterative, blockwise procedure to reconstruct the missing pixel values. Although the complexity of FSR can be considerably decreased by performing its computations in the frequency domain, the reconstruction procedure still takes multiple seconds up to multiple minutes depending on the parameterization. However, FSR has the potential for a massive parallelization greatly improving its reconstruction time. In this paper, we introduce a novel highly parallelized formulation of FSR adapted to the capabilities of modern GPUs and propose a considerably accelerated calculation of the inherent argmax calculation. Altogether, we achieve a 100-fold speed-up, which enables the usage of FSR for real-time applications.<br

Sparse Hartley Modeling for Fast Image Extrapolation - Genser, Nils; Grosche, Simon; Seiler, Jürgen; Kaup, André (IEEE 20th International Workshop on Multimedia Signal Processing (MMSP), 2018)

Towards polarization-based excitation tailoring for extended Raman spectroscopy - Grosche, Simon; Hünermann, Richard; Sarau, George; Christiansen, Silke; Boyd, Robert W.; Leuchs, Gerd; Banzer, Peter (Optics Express, 2020)
Undoubtedly, Raman spectroscopy is one of the most elaborate spectroscopy tools in materials science, chemistry, medicine and optics. However, when it comes to the analysis of nanostructured specimens or individual sub-wavelength-sized systems, the access to Raman spectra resulting from different excitation schemes is usually very limited. For instance, the excitation with an electric field component oriented perpendicularly to the substrate plane is a difficult task. Conventionally, this can only be achieved by mechanically tilting the sample or by sophisticated sample preparation. Here, we propose a novel experimental method based on the utilization of polarization tailored light for Raman spectroscopy of individual nanostructures. As a proof of principle, we create three-dimensional electromagnetic field distributions at the nanoscale using tightly focused cylindrical vector beams impinging normally onto the specimen, hence keeping the traditional beam-path of commercial Raman systems. In order to demonstrate the convenience of this excitation scheme, we use a sub-wavelength diameter gallium-nitride nanostructure as a test platform and show experimentally that its Raman spectra depend sensitively on its location relative to the focal vector field. The observed Raman spectra can be attributed to the interaction with transverse and pure longitudinal electric field components. This novel technique may pave the way towards a characterization of Raman active nanosystems, granting direct access to growth-related parameters such as strain or defects in the material by using the full information of all Raman mode